Vertical Communication Patterns in Small Scale Organizations: Pola Komunikasi Vertikal dalam Organisasi Kecil - Dirgantara, Yuda Putra; Rochmaniah, Ainur (Academia Open, 2026)
General Background: Organizational communication is central to coordination, decision-making, and healthy working relationships, particularly where authority and task execution are connected through vertical interaction. Specific Background: At CV Tama Indo Mulia, communication between superiors and subordinates was examined in a small-scale organizational setting through a qualitative approach involving in-depth interviews with the director and employees from several divisions. Knowledge Gap: Vertical communication in small organizations may appear direct and simple, yet the study identifies limited understanding of how hierarchical patterns, psychological barriers, work culture, and task characteristics shape downward and upward information flow. Aims: This study aims to analyze vertical communication patterns between superiors and subordinates and identify supporting and inhibiting factors at CV Tama Indo Mulia. Results: The dominant pattern was a hierarchical Y-shaped structure. Downward communication tended to be one-way and task-oriented, while upward communication was constrained by reluctance to express opinions, different perceptions, limited interaction time, and differences in technical-term understanding. Interpersonal closeness, digital communication media, and routine briefings supported communication. Novelty: The study provides a focused qualitative account of vertical communication dynamics in a small-scale organization by linking Y-shaped hierarchy with psychological, cultural, and task-related constraints. Implications: The findings indicate the need to strengthen two-way communication and clarify communication structures to support more effective organizational work processes. Highlights: Downward exchanges were mostly instructional and one-way. Employees hesitated to express feedback due to psychological and cultural barriers. Briefings, digital media, and interpersonal closeness supported information flow. Keywords: Communication Pattern, Vertical Communication, Organizational Communication